Proximate, fatty acid and mineral composition of hilsa, Tenualosa ilisha (Hamilton 1822) from the Bay of Bengal and Arabian Gulf - Hossain, M. A.; Almatar, S. M.; Al-Hazza, A. A. (Indian Journal of Fisheries, 2014)
Fish is the best source of n-3 polyunsaturated fatty acids (PUFAs), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The objective of this study was to investigate the proximate, fatty acid and mineral composition of hilsa (Tenualosa ilisha) from the Bay of Bengal and Arabian Gulf. In general, egg protein and lipid contents were significantly (p